Influence of an external low frequency helical perturbation on ballooning modes - Pankratov, I.M.; Omelchenko, A.Ya. (Вопросы атомной науки и техники, 2008)
Equations for investigation of the influence of external helical magnetic perturbations on the ballooning modes are derived in one-fluid MHD with the plasma response and rotation being taken into account.